A comparative note on the free convection of micropolar nanofluid due to the interaction of buoyancy and the dissipative heat energy. Issue 7 (28th June 2021) - Pattnaik, Pradyumna K.; Pattnaik, Jyotsnarani; Mishra, Satya R.; Ali, Bagh
Abstract: A report is prepared for the free convection of micropolar nanofluid past a continuously moving plate. Free convection of polar fluid is obtained due to the interaction of thermal buoyancy acted against the gravitational force. In addition to that, the novelty of the current investigation is to carry over the coupling impact of the governing equations arises because of the inclusion of dissipative heat energy, and the variation of heat source/sink in the presence of suction/blowing. The governing equations are distorted into their ordinary form by the suitable choice of similarity transformation. Furthermore, the homotopy perturbation method (HPM) is employed for the solution of the set of transformed equations. The behavior of the contributing parameters is presented via graphs and the comparison between the analytical HPM and the conventional numerical technique using the in‐built code bvp5c is presented in tabular form. The numerical simulation shows its good concurrency between the methodologies employed. In few major outcomes, it is seen that the shear rate enriches with an increase in nanoparticle volume fraction. Furthermore, the rate of heat transfer decelerates significantly for the enhanced value of thermal radiation whereas the coupling parameter is favorable for the enhancement.